2004
DOI: 10.1029/2003jb002799
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of fine‐grained olivine: Evidence for grain boundary transport

Abstract: [1] To investigate the mechanisms responsible for electrical conduction and deduce the relation between grain size and conductivity, the electrical conductivity of synthetic polycrystalline forsterite, with grain sizes between 1.1 ± 0.4 and 4.7 ± 2.4 mm, was measured at temperatures up to 1470°C and at 0.1 MPa pressure. The complex impedance plots display one clear arc, indicating a single dominant conduction mechanism. Bulk conductivity is inversely proportional to the grain size of the different samples. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 42 publications
(77 reference statements)
4
57
0
Order By: Relevance
“…The magnitude of the effect (six-order increase in cell capacitance) and the depression of all arcs together suggest that the effect does not lie in the sample itself but at the sample/electrode interface. It was previously confirmed that the porosity does not appear to influence the impedance arcs (ten Grotenhuis et al 2004). Although minor porosity (as shown in Fig.…”
Section: Results Of Circuit Modelingmentioning
confidence: 52%
See 3 more Smart Citations
“…The magnitude of the effect (six-order increase in cell capacitance) and the depression of all arcs together suggest that the effect does not lie in the sample itself but at the sample/electrode interface. It was previously confirmed that the porosity does not appear to influence the impedance arcs (ten Grotenhuis et al 2004). Although minor porosity (as shown in Fig.…”
Section: Results Of Circuit Modelingmentioning
confidence: 52%
“…There does not seem to be a coherent differentiation between the electrical conductivity of Fo 100 and Fo 90 (this study) for high temperatures. That is, Fo 90 a with the same grain size as 1a (ten Grotenhuis et al 2004) almost overlap. At lower temperatures, Fo 100 shows 1-3 orders of magnitude lower conductivity than Fo 90 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Systematic measurement errors with the combined apparatus are less than 2%. The conductivity cell, constructed of refractory alumina (Ten Grotenhuis et al, 2004), was equipped with 0.5 mm thick Pt electrodes and guard ring, of similar areal dimensions to the sputtered sample electrodes, to ensure good connection via shielded platinum wires. This was situated inside a 60 mm internal diameter tube furnace, with temperature controlled and monitored using Pt/Pt -10%Rh thermocouples.…”
Section: Materials and Experimental Mehodsmentioning
confidence: 99%